Validity and Practicality of the STEM-Critical Thinking Video in Science Education: Hydraulic Lift - Fadilla Delendra Des Ramadini; Arief Muttaqiin (JIPF (Jurnal Ilmu Pendidikan Fisika), 2023)
This study aims to determine the validity, practicality and students' responses to video experiments oriented towards STEM activities and critical thinking. The research problem is that the implementation of experimental activities in schools is still very rarely used because, limited learning time and the learning that is carried out has not been able to train students' critical thinking skills. The research method used is Research and Development, the research design uses the Plomp model which consists of three stages, namely the preliminary stage, the prototyping stage and ends with the assessment stage, but this research is limited to the prototyping stage. The instruments used to collect data were validity sheets (26 questions), practicality sheets (18 questions) and interview sheets (5 questions). VHL was analyzed descriptively and quantitatively based on the results of validity tests, practicality tests and interviews. The results of the validity test from the three expert reviewers showed that VHL obtained a score of 0.92 with a very high validity category. In terms of practicality, the VHL scores 98% (very practical). In terms of students' responses to VHL, the majority of students stated that they were happy, interested and enthusiastic about learning to use VHL. Therefore, VHL with the theme "Hydraulic Lift" is categorized as feasible and practical to help grade 8 students in practicing critical thinking skills on the concept of material pressure.